Solution
Step 1:
Write the equation for the distance function:
![v(t)\text{ = -cost + 3sint + 3}](https://img.qammunity.org/2023/formulas/mathematics/college/td79467u2dhr6zlaft07cauyu9irbl8te7.png)
Step 2:
_______________________-___________________________________
Part 1
![\begin{gathered} v(t)\text{ = -cost + 3sint + 3} \\ \\ (ds(t))/(dt)=−cost+3sint+3 \\ \\ ds(t)=(−cost+3sint+3)dt \\ \\ s(t)=\int(−cost+3sint+3)dt \\ \\ s(t)\text{ = -sint - 3cost + 3t + c} \\ \\ s(0)\text{ = -sin\lparen0\rparen - 3cos\lparen0\rparen + 3\lparen0\rparen + c} \\ c\text{ = 3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fhopirsk30wfn9v9n8zi4dbw0je6ic9ibf.png)
Find s(t), if s(0) = 0
s(t) = -sint - 3cost + 3t + 3
________________________________________________________
Part 2
![\begin{gathered} v(t)\text{ = -cost + 3sint + 3} \\ \\ a(t)\text{ = }(dv(t))/(dt) \\ \\ (dv(t))/(dt)\text{ = sint + 3cost} \\ \\ a(t)\text{ = sint + 3cost} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3m05ttcha00a98ncrplndy6qumkktq7mnl.png)
Find a(t)
a(t) = sint + 3cost